2016
DOI: 10.1017/s1355617716000321
|View full text |Cite
|
Sign up to set email alerts
|

Visuospatial Processing Deficits Linked to Posterior Brain Regions in Premanifest and Early Stage Huntington’s Disease

Abstract: Objective: Visuospatial processing deficits have been reported in Huntington's disease (HD). To date, no study has examined associations between visuospatial cognition and posterior brain findings in HD. Method: We compared 119 premanifest (55 > and 64 < 10.8 years to expected disease onset) and 104 early symptomatic (59 stage-1 and 45 stage-2) gene carriers, with 110 controls on visual search and mental rotation performance at baseline and 12 months. In the disease groups we also examined associations between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 47 publications
5
38
0
Order By: Relevance
“…Our finding that impaired visuospatial perception in HD significantly correlated with a greater, jerkier sway path under DT, suggests that HD participants may depend heavily on their visuospatial system, especially during DT to maintain balance. Visuospatial skills are important for gait and postural control and are modulated by the posterior parietal and occipital cortices, areas of volume loss in HD . The ability to identify and manipulate where an object is in space involves activation of the parietal lobes, primary motor and premotor cortices, and the basal ganglia .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding that impaired visuospatial perception in HD significantly correlated with a greater, jerkier sway path under DT, suggests that HD participants may depend heavily on their visuospatial system, especially during DT to maintain balance. Visuospatial skills are important for gait and postural control and are modulated by the posterior parietal and occipital cortices, areas of volume loss in HD . The ability to identify and manipulate where an object is in space involves activation of the parietal lobes, primary motor and premotor cortices, and the basal ganglia .…”
Section: Discussionmentioning
confidence: 99%
“…Visuospatial skills are important for gait and postural control and are modulated by the posterior parietal and occipital cortices, areas of volume loss in HD . The ability to identify and manipulate where an object is in space involves activation of the parietal lobes, primary motor and premotor cortices, and the basal ganglia . Prefrontal cortical degeneration in HD would likely contribute to these deficits, given that this area mediates the ability to perform a cognitive motor DT involving executive function .…”
Section: Discussionmentioning
confidence: 99%
“…The manifest stage of HD is clinically characterized by progressive motor disturbances such as chorea and dystonia, cognitive decline, and psychiatric symptoms (Bates et al, 2015;Roos, 2010). Nonetheless, neuropsychological studies assessing visual cognitive function in HD reported impairments in several visual domains, specifically tasks involving visual object perception (Gómez-Tortosa, del Barrio, Barroso, & García Ruiz, 1996;Lemiere, Decruyenaere, Evers-Kiebooms, Vandenbussche, & Dom, 2004), facial emotion recognition (Bora, Velakoulis, & Walterfang, 2016;Kordsachia, Labuschagne, & Stout, 2017), visuospatial processing, and visual working memory (E. Johnson et al, 2015;Labuschagne et al, 2016). Nonetheless, neuropsychological studies assessing visual cognitive function in HD reported impairments in several visual domains, specifically tasks involving visual object perception (Gómez-Tortosa, del Barrio, Barroso, & García Ruiz, 1996;Lemiere, Decruyenaere, Evers-Kiebooms, Vandenbussche, & Dom, 2004), facial emotion recognition (Bora, Velakoulis, & Walterfang, 2016;Kordsachia, Labuschagne, & Stout, 2017), visuospatial processing, and visual working memory (E. Johnson et al, 2015;Labuschagne et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive decline mainly involves progressive impairment in executive function (Dumas, van den Bogaard, Middelkoop, & Roos, 2013). Nonetheless, neuropsychological studies assessing visual cognitive function in HD reported impairments in several visual domains, specifically tasks involving visual object perception (Gómez-Tortosa, del Barrio, Barroso, & García Ruiz, 1996;Lemiere, Decruyenaere, Evers-Kiebooms, Vandenbussche, & Dom, 2004), facial emotion recognition (Bora, Velakoulis, & Walterfang, 2016;Kordsachia, Labuschagne, & Stout, 2017), visuospatial processing, and visual working memory (E. Johnson et al, 2015;Labuschagne et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As such, deficits in 'higherlevel' visual functions that require cognitive control are consistently documented. These include deficits in visual search [7,8], visual selective attention [9], mental rotation [8,10] and some aspects of visuo-spatial working memory [7,11]. In such cases, it is difficult to tease the relative contributions of reduced bottom-up, sensory neurotransmission and topdown cognitive control to performance impairments, although it is likely that cognitive disturbances have a marked effect on performance on some visual sensory tasks.…”
Section: Introductionmentioning
confidence: 99%